2011
DOI: 10.1177/0307174x1103800608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Filler Particle Shape on the Nature of Failure of Polypropylene-Based Composites

Abstract: An investigation was made of the influence of the filler particle shape on the nature of failure of PP-based composites. It was established that the filler particle shape affects the types of defect formed and the nature of failure of PP-based composites. The introduction of talc or wollastonite particles into PP leads to brittle failure of the composite up to its upper yield point. When spherical particles are used, the material retains plastic properties, and rupture occurs on neck propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Another comparative study on the effect of filler particle shape on the nature of failure of PP composites was conducted . It was found that the addition of talc or wollastonite particles as filler will lead to the brittle failure of the PP composites at their upper yield point.…”
Section: Tensile and Flexural Properties Of Polymer Compositesmentioning
confidence: 99%
“…Another comparative study on the effect of filler particle shape on the nature of failure of PP composites was conducted . It was found that the addition of talc or wollastonite particles as filler will lead to the brittle failure of the PP composites at their upper yield point.…”
Section: Tensile and Flexural Properties Of Polymer Compositesmentioning
confidence: 99%